Diluted serum from calorie‐restricted animals promotes mitochondrial β‐cell adaptations and protect against glucolipotoxicity. (15th February 2016) - Cerqueira, Fernanda M.; Chausse, Bruno; Baranovski, Boris M.; Liesa, Marc; Lewis, Eli C.; Shirihai, Orian S.; Kowaltowski, Alicia J.
Abstract : β‐cells quickly adjust insulin secretion to oscillations in nutrients carried by the blood, acting as fuel sensors. However, most studies of β‐cell responses to nutrients do not discriminate between fuel levels and signaling components present in the circulation. Here we studied the effect of serum from calorie‐restricted rats versus serum from rats fed ad libitum, diluted tenfold in the medium, which did not contribute significantly to the pool of nutrients, on β‐cell mitochondrial function and dynamics under regular and high‐nutrient culture conditions. Insulin secreting beta‐cell derived line (INS1) cells incubated with serum from calorie‐restricted rats (CR serum) showed higher levels of peroxisome proliferator‐activated receptor gamma coactivator 1‐α (PGC‐1α) and active nitric oxide synthase. The expression of mitofusin‐2 (Mfn‐2) and optic atrophy 1 (OPA‐1), proteins involved in mitochondrial fusion, was increased, while the levels of the mitochondrial fission mediator dynamin related protein 1 (DRP‐1) were reduced. Consistent with changes in mitochondrial dynamics protein levels, CR serum treatment increased mitochondrial fusion rates, as well as their length and connectivity. These changes in mitochondrial morphology were associated with prolonged glucose‐stimulated insulin secretion and mitochondrial respiration. When combining CR serum and high levels of glucose and palmitate (20 and 0.4 mm, respectively), an in vitro model of type II diabetes, we observed that signaling promoted by CR serum was enough to overcome glucolipotoxicity, as indicated by CR‐mediated prevention of mitochondrial fusion arrest and reduced respiratory function in INS1 cells under glucolipotoxicity. Overall, our results provide evidence that non‐nutrient factors in serum have a major impact on β‐cell mitochondrial adaptations to changes in metabolism. Abstract : Sera obtained from Calorie‐Restricted (CR) or Ad Libitum (AL) ‐fed mouse was diluted 10× in culture media, which was used in beta‐cell culture. CR treated cells presented increased mitochondrial fusion and bioenergetics efficiency. Moreover, diluted CR serum prevented mitochondrial fragmentation induced by high glucose and fatty acids (glucolipotoxicity) and improved glucose stimulated insulin secretion in beta‐cells and whole islets.